6-week High-intensity Interval Training (HIIT) of the Lower Extremities Improves VO2max of the Upper Extremities - Marterer, Natalie; Menz, Verena; Amin, Sachin; Faulhaber, Martin (International Journal of Sports Medicine, 2020)
High intensity interval training (HIIT) is widely used to improve VO2max. The purpose of this study was to examine if lower extremity HIIT resulted in improved maximal oxygen uptake (VO2max) and peak power output (PPO) of the upper extremities. Twenty healthy and trained participants (11 female and 9 male, VO2max 3160±1175 ml/min) underwent a 6-week HIIT program of the lower extremities on a cycle ergometer. Before and after the training period a maximal cycle ergometry (CE) and a maximal hand crank ergometry (HCE) were conducted to determine VO2max and PPO. Additionally, hematological parameters were determined. Increases in VO2max of the lower extremities (3160±1175 to 3449±1231 ml/min, p<0.001, η2p=0.779) as well as of the upper extremities (2255±938 to 2377±1015 ml/min, p=0.010, η2p=0.356) from pre- to post-test were found. PPO of the lower extremities increased (243±95 to 257±93 W, p<0.001, η2p=0.491), whereas it remained unchanged for the upper extremities (103±50 to 108±54 W, p=0.209, η2p=0.150). All hematological parameters increased. The results demonstrate that VO2max of the upper extremities increased after 6-weeks of cycling HIIT. However, upper body PPO was unchanged.
Keywords: high intensity interval training; maximal oxygen uptake; blood volume; T-Hb-mass; transfer of training gains